The first actress : a novel of Sarah Bernhardt - Gortner, C. W. (Ballantine Books, 2020)
"From her beginnings as the daughter of a courtesan to her extraordinary transformation into the most celebrated actress of her era, Sarah Bernhardt is brought to life by an internationally bestselling author praised for his historical novels featuring famous women. Told in her own voice, this is Sarah Bernhardt's incandescent story--a fascinating, intimate account of a woman whose unrivaled talent and indomitable spirit has enshrined her in history as the Divine Sarah."--Publisher description.